2016
DOI: 10.1007/s00408-016-9842-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Thromboembolic Pulmonary Hypertension: Experience from a Single Center in Mexico

Abstract: Introduction Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by precapillary pulmonary hypertension secondary to vaso-occlusive pulmonary vasculopathy and is classified as Pulmonary Hypertension Group 4. The aim of this study is to report the clinical experience of CTEPH in Mexico. Methods Consecutive patients diagnosed with CTEPH were identified from the Registro de Pacientes con Hipertension Pulmonar del Instituto de Seguridad y Servicio Social de los Trabajadores del Estado (REPHPIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…Although patients with CTEPH are a heterogeneous group with respect to their hemodynamic status and surgical accessibility of pulmonary thromboemboli, resulting in demarcation as operable or inoperable patients, they also present with many similarities at diagnosis, suggesting a common underlying disease process. 26 In line with previous registries from the US, Canada, Europe, Japan, and Mexico, 5 , 26 30 CTEPH was almost equally frequent in men and women in their 6th decade of life, approximately 63 years, which is comparable to our cohort. The slight female predominance observed in this study is also consistent with the findings from the international registry.…”
Section: Discussionsupporting
confidence: 92%
“…Although patients with CTEPH are a heterogeneous group with respect to their hemodynamic status and surgical accessibility of pulmonary thromboemboli, resulting in demarcation as operable or inoperable patients, they also present with many similarities at diagnosis, suggesting a common underlying disease process. 26 In line with previous registries from the US, Canada, Europe, Japan, and Mexico, 5 , 26 30 CTEPH was almost equally frequent in men and women in their 6th decade of life, approximately 63 years, which is comparable to our cohort. The slight female predominance observed in this study is also consistent with the findings from the international registry.…”
Section: Discussionsupporting
confidence: 92%
“…With a median follow up of 20 months, the mortality rate in the Mexican registry reported by Al-Naamani et al [11] was 28 %, which is consistent with the outcomes reported in other registries in developed countries that are enriched with more resources. Examination of the survival curve for the cohort diagnosed via right heart catheterization discloses a 2-year survival of about 80 %, consistent with the survival rate reported in the international (European countries and Canada) registry for non-operated patients, but more than 10 % lower compared to operated patients [12].…”
supporting
confidence: 86%
“…In this issue of Lung, Al-Naamani et al report on the experience of a CTEPH cohort registry (REPHPISSSTE registry) in two medical centers in Mexico [11]. Out of the 45 patients who were evaluated for operability (whether retrospectively by chart review or prospectively), a total of 29 patients (64 %) were deemed operable.…”
mentioning
confidence: 99%
“…Indeed, the challenge of attracting potential candidates for PEA surgery in a resource-limited setting was recently highlighted in the first report on the CTEPH experience in Mexico, where only one patient in fifty could undergo PEA surgery. 7 Of note, PEA surgery was already being performed in many centers that did not have heart/lung transplantation or ECMO capabilities, and this indicates a lack of agreement among Asia-Pacific surgeons regarding the necessity for such resources.…”
Section: Discussionmentioning
confidence: 99%